GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 12 Dec 2019, 18:05 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  # New Algebra Set!!!

Author Message
TAGS:

### Hide Tags

Math Expert V
Joined: 02 Sep 2009
Posts: 59712

### Show Tags

54
203
1. If $$x=\sqrt{x^3+6x^2}$$, then the sum of all possible solutions for x is:

A. -2
B. 0
C. 1
D. 3
E. 5

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200948

2. The equation x^2 + ax - b = 0 has equal roots, and one of the roots of the equation x^2 + ax + 15 = 0 is 3. What is the value of b?

A. -64
B. -16
C. -15
D. -1/16
E. -1/64

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200950

3. If a and b are positive numbers, such that a^2 + b^2 = m and a^2 - b^2 = n, then ab in terms of m and n equals to:

A. $$\frac{\sqrt{m-n}}{2}$$
B. $$\frac{\sqrt{mn}}{2}$$
C. $$\frac{\sqrt{m^2-n^2}}{2}$$
D. $$\frac{\sqrt{n^2-m^2}}{2}$$
E. $$\frac{\sqrt{m^2+n^2}}{2}$$

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200956

4. What is the maximum value of -3x^2 + 12x -2y^2 - 12y - 39 ?

A. -39
B. -9
C. 0
D. 9
E. 39

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200962

5. If x^2 + 2x -15 = -m, where x is an integer from -10 and 10, inclusive, what is the probability that m is greater than zero?

A. 2/7
B. 1/3
C. 7/20
D. 2/5
E. 3/7

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200970

6. If mn does not equal to zero, and m^2n^2 + mn = 12, then m could be:

I. -4/n
II. 2/n
III. 3/n

A. I only
B. II only
C. III only
D. I and II only
E. I and III only

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200973

7. If x^4 = 29x^2 - 100, then which of the following is NOT a product of three possible values of x?

I. -50
II. 25
III. 50

A. I only
B. II only
C. III only
D. I and II only
E. I and III only

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200975

8. If m is a negative integer and m^3 + 380 = 381m , then what is the value of m?

A. -21
B. -20
C. -19
D. -1
E. None of the above

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200980

9. If $$x=(\sqrt{5}-\sqrt{7})^2$$, then the best approximation of x is:

A. 0
B. 1
C. 2
D. 3
E. 4

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200982

10. If f(x) = 2x - 1 and g(x) = x^2, then what is the product of all values of n for which f(n^2)=g(n+12) ?

A. -145
B. -24
C. 24
D. 145
E. None of the above

Solution: https://gmatclub.com/forum/new-algebra- ... l#p1200987

Kudos points for each correct solution!!!
_________________

Originally posted by Bunuel on 18 Mar 2013, 07:56.
Last edited by Bunuel on 18 Feb 2019, 05:31, edited 1 time in total.
Updated.
Math Expert V
Joined: 02 Sep 2009
Posts: 59712

### Show Tags

23
49
SOLUTIONs:

1. If $$x=\sqrt{x^3+6x^2}$$, then the sum of all possible solutions for x is:

A. -2
B. 0
C. 1
D. 3
E. 5

Take the given expression to the 4th power: $$x^4=x^3+6x^2$$;

Re-arrange and factor out x^2: $$x^2(x^2-x-6)=0$$;

Factorize: $$x^2(x-3)(x+2)=0$$;

So, the roots are $$x=0$$, $$x=3$$ and $$x=-2$$. But $$x$$ cannot be negative as it equals to the even (4th) root of some expression ($$\sqrt{expression}\geq{0}$$), thus only two solution are valid $$x=0$$ and $$x=3$$.

The sum of all possible solutions for x is 0+3=3.

_________________
Manager  Joined: 12 Mar 2012
Posts: 78
Location: India
Concentration: Technology, Strategy
GMAT 1: 710 Q49 V36 GPA: 3.2
WE: Information Technology (Computer Software)

### Show Tags

5
3. a^2 + b^ 2 = m
a^2 - b^2 = n
Solving both the equations( adding them, and then subtracting them ):
2a^2 = m + n
2b^2 = m - n.
a = ((m+n)/2)^(1/2)
b = ((m-n)/2)^(1/2)

ab = ((m^2 - n^2)^(1/2))/2

##### General Discussion
SVP  P
Joined: 24 Jul 2011
Posts: 1917
GMAT 1: 780 Q51 V48 GRE 1: Q800 V740 ### Show Tags

2
Edited

1. x^4 = x^3 + 6x^2
=> x^2 (x^2 - x - 6) = 0
The roots of x^2 - x - 6 are -2 and 3, but -2 cannot be the value of x. So 3 and 0 are the only possible roots.
=> Sum of all possible solutions = 3.

Option D
_________________

Awesome Work | Honest Advise | Outstanding Results

Reach Out, Lets chat!
Email: info at gyanone dot com | +91 98998 31738 | Skype: gyanone.services

Originally posted by GyanOne on 18 Mar 2013, 08:06.
Last edited by GyanOne on 18 Mar 2013, 13:34, edited 3 times in total.
Math Expert V
Joined: 02 Sep 2009
Posts: 59712

### Show Tags

3
1
GyanOne wrote:
1. x^4 = x^3 + 6x^2
=> x^2 (x^2 - x - 6) = 0
Sum of roots of x^2 - x - 6 = 0 is 1 and the only other solution is x=0
=> Sum of all possible solutions = 1.

Option C

Some questions are tricky!!!
_________________
Manager  Joined: 12 Mar 2012
Posts: 78
Location: India
Concentration: Technology, Strategy
GMAT 1: 710 Q49 V36 GPA: 3.2
WE: Information Technology (Computer Software)

### Show Tags

2
2. Let one of the roots be x, then other root is also x.
Sum of roots = 2x = -a
Product of roots = x^2 = - b

For other equation one root is 3 and product of the roots is 15, so other root is 5.
Sum of roots = 8 = -a
or a = -8.
From above 2x = 8 or x = 4,
b = - x^2 = -16.
SVP  P
Joined: 24 Jul 2011
Posts: 1917
GMAT 1: 780 Q51 V48 GRE 1: Q800 V740 ### Show Tags

2
2
4. -3x^2 + 12x -2y^2 - 12y - 39 = 3(-x^2 + 4x - 13) + 2(-y^2-6y)

Now -x^2 +4x - 13 has its maximum value at x = -4/-2 = 2 and -y^2 - 6y has its maximum value at y=6/-2 = -3
Therefore max value of the expression
= 3(-4 + 8 -13) + 2 (-9+18) = -27 + 18 = -9

Should be B
_________________

Awesome Work | Honest Advise | Outstanding Results

Reach Out, Lets chat!
Email: info at gyanone dot com | +91 98998 31738 | Skype: gyanone.services

Originally posted by GyanOne on 18 Mar 2013, 08:23.
Last edited by GyanOne on 18 Mar 2013, 10:13, edited 1 time in total.
SVP  P
Joined: 24 Jul 2011
Posts: 1917
GMAT 1: 780 Q51 V48 GRE 1: Q800 V740 ### Show Tags

1
9. x = (sqrt(5) - sqrt(7))^2
= 5 + 7 - 2sqrt(35)
=~ 12 - 2*6 = 0

Option A
_________________

Awesome Work | Honest Advise | Outstanding Results

Reach Out, Lets chat!
Email: info at gyanone dot com | +91 98998 31738 | Skype: gyanone.services
Manager  Joined: 12 Mar 2012
Posts: 78
Location: India
Concentration: Technology, Strategy
GMAT 1: 710 Q49 V36 GPA: 3.2
WE: Information Technology (Computer Software)

### Show Tags

2
6. M^2 * n^2 + mn = 12
mn( mn + 1 ) = 12
mn = 3 or mn = -4 ( 3 * 4 = 12; -4 * -3 = 12 )
So m = 3/n or m = -4/n

SVP  P
Joined: 24 Jul 2011
Posts: 1917
GMAT 1: 780 Q51 V48 GRE 1: Q800 V740 ### Show Tags

8. If m is a negative integer and m^3 + 380 = 381m , then what is the value of m?

m^3 - 381m + 380 = 0
Sum of roots = 0
Product of roots = -380

Therefore 19,1,-20 is definitely a possible solution set. Sum of roots = 0, Product of roots = -380

B is therefore the right answer.
_________________

Awesome Work | Honest Advise | Outstanding Results

Reach Out, Lets chat!
Email: info at gyanone dot com | +91 98998 31738 | Skype: gyanone.services
Manager  Joined: 12 Mar 2012
Posts: 78
Location: India
Concentration: Technology, Strategy
GMAT 1: 710 Q49 V36 GPA: 3.2
WE: Information Technology (Computer Software)

### Show Tags

5
8. m^3 + 380 = 381m
m^3 + 380 = 380m + m
m^3 -m = 380m - 380
m(m-1)(m+1) = 380 (m-1)
m(m+1) = 380 ( -20 * -19; m is negative )
m = -20.

Senior Manager  Joined: 28 Apr 2012
Posts: 265
Location: India
Concentration: Finance, Technology
GMAT 1: 650 Q48 V31 GMAT 2: 770 Q50 V47 WE: Information Technology (Computer Software)

### Show Tags

1. If $$x=\sqrt{x^3+6x^2}$$, then the sum of all possible solutions for x is:

A. -2
B. 0
C. 1
D. 3
E. 5
$$x=\sqrt{x^3+6x^2}$$
=>$$x^4=x^3+6x^2$$
=>$$x^4-x^3-6x^2=0$$

Sum of roots for $$ax^n+bx^(n-1)+cx^(n-2)+... + constant$$ = $$-b/a$$
In the given prob : b= -1, a=1

Sum of roots = $$-b/a = -(-1)/1 = 1$$
C
Manager  Joined: 12 Mar 2012
Posts: 78
Location: India
Concentration: Technology, Strategy
GMAT 1: 710 Q49 V36 GPA: 3.2
WE: Information Technology (Computer Software)

### Show Tags

1
10.
2x^2 - 1 = (x+12)^2
2x^2 - 1 = x^2 + 24x +144
x^2 - 24x - 145 = 0
Product of roots = -145
Senior Manager  Joined: 28 Apr 2012
Posts: 265
Location: India
Concentration: Finance, Technology
GMAT 1: 650 Q48 V31 GMAT 2: 770 Q50 V47 WE: Information Technology (Computer Software)

### Show Tags

1
10.If$$f(x) = 2x - 1$$ and$$g(x) = x^2$$, then what is the product of all values of n for which $$f(n^2)=g(n+12)$$?

A. -145
B. -24
C. 24
D. 145
E. None of the above

$$f(n^2) = 2n^2 -1 g(n+12) = (n+12)^2 =>2n^2 -1 = (n+12)^2 =>2n^2 -1 = n^2 + 24n + 144 => n^2 - 24n - 145 = 0$$

Product of all n = product of roots of the above equation.
For ax^2 + bx + c = 0 => Product of roors = c/a
Product of roots = -145/1 = -145
Ans = A
VP  Status: Far, far away!
Joined: 02 Sep 2012
Posts: 1010
Location: Italy
Concentration: Finance, Entrepreneurship
GPA: 3.8

### Show Tags

3
1)$$x^4=x^3+6x^2$$
$$x^4-x^3-6x^2=0$$
$$x^2(x^2-x-6)=0$$
$$x^2=0 (1) x = 0$$
$$x^2-x-6=0 (2) x = 3 (3) x = -2$$
$$0+3-2=1$$
C

2)The equation x^2 + ax - b = 0 has equal roots
$$a^2+4b=0$$
one of the roots of the equation x^2 + ax + 15 = 0 is 3
$$(-a+-\sqrt{a^2-4*15})/2=3$$
$$+-\sqrt{a^2-60}=6+a$$
$$(\sqrt{a^2-60})^2=(6+a)^2$$
$$-96=12a$$
$$a=-8$$

$$a^2+4b=0$$
$$64+4b=0$$
$$b=-16$$
B

3)We can use some numbers
$$2^2+1^2=5=m 2^2-1^2=5=n$$
$$ab=2$$

$$\sqrt{m^2-n^2}/2 = \sqrt{25-9}/2 = 2 = ab$$
C

4) -3x^2 + 12x -2y^2 - 12y - 39 MAX
$$-3x^2 + 12x$$ has max in (2,12)
$$-2y^2 - 12y - 39$$ has max in (-6,-3)
-3x^2 + 12x -2y^2 - 12y - 39 MAX = 12 - 3 =9
D
Manager  Joined: 12 Mar 2012
Posts: 78
Location: India
Concentration: Technology, Strategy
GMAT 1: 710 Q49 V36 GPA: 3.2
WE: Information Technology (Computer Software)

### Show Tags

5. I have taken a longer approach, there should be a better solution.
x^2 + 2x -15 = -m
x^2 + 5x - 3x - 15 = -m
(x+5)(x-3) = -m
x will have integer values, since m is also an integer.
Putting positive values for x such as ( 1, 2....) we will get values for m which lies between -10 and 10, they are -9, 0 and 7.
We will get same result for negative values of x, the equation is a parabola, it will be symmetric
Hence the probability is 1/3
VP  Status: Far, far away!
Joined: 02 Sep 2012
Posts: 1010
Location: Italy
Concentration: Finance, Entrepreneurship
GPA: 3.8

### Show Tags

4
6. If mn does not equal to zero, and m^2n^2 + mn = 12, then m could be:

I. -4/n
II. 2/n
III. 3/n

A. I only
B. II only
C. III only
D. I and II only
E. I and III only

$$m^2n^2 + mn = 12$$
$$mn(mn+1) = 12$$
mn = 3
$$3(3+1)=12$$
OR
mn = -4
$$-4(-4+1)=12$$

$$m= 3/n$$
OR
$$m=-4/n$$
E
VP  Status: Far, far away!
Joined: 02 Sep 2012
Posts: 1010
Location: Italy
Concentration: Finance, Entrepreneurship
GPA: 3.8

### Show Tags

4) -3x^2 + 12x -2y^2 - 12y - 39 MAX
-3x^2 + 12x has max in (2,12)
-2y^2 - 12y - 39 has max in (-6,-3)
-3x^2 + 12x -2y^2 - 12y - 39 MAX = 12 - 3 =9
D
VP  Status: Far, far away!
Joined: 02 Sep 2012
Posts: 1010
Location: Italy
Concentration: Finance, Entrepreneurship
GPA: 3.8

### Show Tags

1
9. If x=(\sqrt{5}-\sqrt{7})^2, then the best approximation of x is:

A. 0
B. 1
C. 2
D. 3
E. 4

$$x=5+7-2\sqrt{35}$$
$$\sqrt{35}=6$$ almost...
$$x=5+7-2*6$$
$$x=0$$

A
VP  Status: Far, far away!
Joined: 02 Sep 2012
Posts: 1010
Location: Italy
Concentration: Finance, Entrepreneurship
GPA: 3.8

### Show Tags

1
If f(x) = 2x - 1 and g(x) = x^2, then what is the product of all values of n for which f(n^2)=g(n+12) ?

A. -145
B. -24
C. 24
D. 145
E. None of the above

$$2n^2-1=(n+12)^2$$

$$2n^2-1=n^12+144+24n$$

$$n^2-24n-145=0$$

$$n1=29, n2=-5$$

$$n1*n2=-145$$

A Re: New Algebra Set!!!   [#permalink] 18 Mar 2013, 09:54

Go to page    1   2   3   4   5   6   7   8    Next  [ 146 posts ]

Display posts from previous: Sort by

# New Algebra Set!!!  